Реакція гібридів соняшнику на припосівне удобрення в Степу України - Гайченя, Ігор Романович; Haichenia, Ihor (ЦНТУ, 2023)
В даній випускній кваліфікаційній роботі вивчено вплив двох форм припосівного добрива на формування врожайності трьох гібридів соняшника в Степу України. Мета досліджень – визначити кращу форму добрива для внесення при сівбі соняшника. Найвищий рівень врожайності насіння соняшника отримали при вирощуванні гібриду П64ЛП130 з припосівним внесенням амофосу в дозі 50 кг/га у фізичній масі. In this graduation thesis, the influence of two forms of seed fertilizer on the formation of productivity of three sunflower hybrids in the Steppe of Ukraine was studied. The purpose of the research is to determine the best form of fertilizer to be applied when sowing sunflower seeds. The highest level of productivity of sunflower seeds was obtained when growing the P64LP130 hybrid with the sowing of ammophos at a dose of 50 kg/ha in physical weight.
Response of sunflower hybrids to pre-sowing fertilisation in the Steppe of Ukraine
Keywords: соняшник; гібриди; припосівне удобрення; sunflower; hybrids; pre-sowing fertilizer